Implementasi program aplikasi rekapitulasi pembayaran SPP pada SMK Prima Tiara Makassar - Mashud Mashud; Rohayati Rohayati; First Wanita; Erwin Gatot; Ibnu Taimiyah Darwis; Paramita Paramita (Rengganis Jurnal Pengabdian Masyarakat, 2021)
This community service program aims to design and implement the SPP payment application at SMK Prima Tiara Makassar. The problem arises when the treasurer collects data on students who have paid and who have not paid tuition, this causes a lot of time to be wasted. In addition, the payment record book will become damaged so that the reporting of monthly payments will be late. So that the existence of a payment application helps in the payment process for SPP SMK Prima Tiara Makassar.